Is the Individual Market More Than a Bridge Market? An Analysis of Disenrollment Decisions - M. Susan Marquis; Melinda Beeuwkes Buntin; José J. Escarce; Kanika Kapur; Thomas A. Louis (SAGE Publishing, 2005)
The individual insurance market is perceived by many to provide primarily transition coverage, but there is limited research about how long people stay in this market and what affects their disenrollment decisions. We examine these issues using administrative records and survey data for those enrolled in the individual market in California. We conclude that there is less turnover in this market than is commonly believed. We find that economic factors and coverage characteristics are important in the decision to disenroll, but that perceptions about insurance and the health care system also affect this decision.